Family Economic Socialization and Youth Productive Behavior in East Java: Islamic Religiosity as a Moral Shield - Adibah; AM. Maqdum Biahmada; Rafikhein Novia Ayuanti; Sufinatin Aisida (Journal of Public Power, 2026)
In an era of economic volatility and pervasive digitalization, the younger generation confronts the intensifying pressures of consumerism culture driven by the fear of missing out (FOMO), which threatens productive work ethics and exacerbates youth unemployment. This study analyzes the direct and indirect effects of family economic socialization on youth productive behavior, positioning Islamic religiosity as a mediating variable. Employing a causal quantitative design, this study examined 385 Muslim youths in East Java classified as digital natives. Data collected through structured questionnaires were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) via SmartPLS 4. Results reveal that family economic socialization positively and significantly influences Islamic religiosity (β = 0.754, p = 0.000) and youth productive behavior (β = 0.465, p = 0.000). Islamic religiosity further exerts a positive and significant influence on productive behavior (β = 0.249, p = 0.000), while the indirect effect confirms its critical mediating role (β = 0.188, p = 0.000). The study extends Social Cognitive Theory by incorporating Islamic religiosity as an internal self-regulatory mechanism that mediates family-based economic learning and productive behavior.